The Challenges of Agricultural Extension Workers in Coastal Area (Case Study at Lingga Regency) - Triandini, Puja; Putra, Adityo Azana; Wildani, Rizka; Yanis, Muhammad Nazarul; -, Sarlinda; Putri, Nova Anisa (Fakultas Pertanian Universitas Jember, 2025)
The community of Lingga Regency are still unfamiliar to agriculture because the majority of their livelihood comes from the sea, so that agricultural commodities are imported from other provinces. To fulfill their own agriculture need, the knowledge and skills of agricultural sector are required that assisted by extension workers. The fact is agricultural extension workers in Lingga Regency is only seven people that should handle 75 villages. This research aims to analyze the challenges that faced by agricultural extension workers in carrying out their activities. The mixed methods is used for this reseacrh with a sequential explanatory strategy. Methods of sampling done using census method. Data was collected through in-depth interview, moderate participant observation, recording and documentation. Data analyze was carried out by data reduction, data interpretation and made conclusions. The result shows 1) challenge of facilities and infrastructure is the most felt by extension workers is the wide of working areas; 2) challenge of farmers as agriculture subject is the age of the farmers, the higher of farmer’s age it will increase the challenge to extension workers; and 3) challenge of support and resources is the most felt by extension workers is personal capital. The agricultural extension workers in Lingga Regency hope that the government will add the extension worker, provide moral and material support and establish an Agricultural Extension Center (BPP) so that the information and extension activities in Lingga Regency will be organized very well.